Factors contributing to cost in partial versus total tonsillectomy. (25th March 2013) - Stucken, Emily Z.; Grunstein, Eli; Haddad, Joseph; Modi, Vikash K.; Waldman, Erik H.; Ward, Robert F.; Stewart, Michael G.; April, Max M.
Abstract : Objectives/Hypothesis: To examine differences between total tonsillectomy and partial intracapsular tonsillectomy techniques that may lead to differences in overall cost and resource utilization between these procedures. Preoperative, perioperative, and postoperative management and outcome factors were examined. Study Design: Retrospective review at two university‐based tertiary care hospitals from January 2007 to June 2010. Methods: Pediatric patients with obstructive symptoms were divided into those undergoing total tonsillectomy and those undergoing partial intracapsular tonsillectomy. The records of 289 patients who underwent total tonsillectomy and 289 patients who underwent partial intracapsular tonsillectomy were reviewed. Results: The average age of patients undergoing total and partial tonsillectomies was 5.0 years for both groups. Significant differences for patients undergoing total versus partial tonsillectomies were as follows: operative time (32.4 vs. 26.4 minutes, P  < .0001), postanesthesia care unit (PACU) time (174 vs. 91.6 minutes, P  < .0001), percent admitted postoperatively (21.5% vs. 1.7%, P  < .0001), number requiring pediatric intensive care unit stay (3.5% vs. 0.3%, P  < .05), number of readmissions after discharge (3.5% vs. 0.3%, P  < .05), and number of postoperative emergency room visits separate from those requiring readmission (4.8% vs. 0%, P  < .05). Factors that were not found to be significantly different included number of patients with postoperative hemorrhage and number requiring second operations for tonsillar regrowth. Conclusions: Previous studies have shown equivalent effectiveness between these two procedures; our study suggests decreased cost and resource utilization with partial tonsillectomy through reduced operative and PACU times and number of postoperative admissions and emergency department visits. As in all retrospective reviews, the findings are potentially confounded by unmeasured variables, including patient and demographic factors. Level of Evidence: 4. Laryngoscope, 123:2868–2872, 2013